Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Mapel PAI Kelas VIII SMP Empat Lima Karanggeneng - anggraini, Novia; Nikmah, Khoirotun (Jurnal Murid, 2026)
Currently, many teachers still apply conventional learning models, especially in Islamic Education subjects. In today’s modern era, a more effective and relevant learning model is required. One model considered capable of improving learning effectiveness is Problem Based Learning (PBL). This study aims to determine the application of the Problem Based Learning model in PAI subjects for eighth-grade students at SMP Empat Lima Karanggeneng and to examine the effect of PBL on students’ learning outcomes. This research employed a quantitative method with a quasi-experimental approach. The research design involved two classes: the experimental class using the PBL model and the control class using a conventional model. The research instruments consisted of pretests and posttests. Data analysis used the t-test and linear regression to identify differences in average learning outcomes between the two groups. The results showed that the Problem Based Learning model significantly influenced students’ learning outcomes in the PAI subject, proven by the t-test results (t-count 11.285 > t-table 2.037) with a significance level of 0.000 < 0.05. This means that Ha was accepted and H0 was rejected, indicating a significant effect of PBL on student achievement. Moreover, the gain score of the experimental class (1.81) was higher than that of the control class (0.52). Therefore, it can be concluded that the Problem Based Learning model is more effective to improve students’ learning outcomes in Islamic education.